1998
DOI: 10.1002/etc.5620170221
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in the swimming performance of fishes: An overlooked source of variation in toxicity studies

Abstract: A commonly used indicator of sublethal stress in fish is impaired swimming performance. Analysis of performance data usually employs a simple comparison, in which the mean of a stressed group of fish is compared to that of a control group. Although such a comparison is satisfactory in many cases, a comparison emphasizing individual variation in performance can yield valuable information unattainable by a means comparison. In this experiment, we determined critical swimming speeds of subadult male fathead minno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 10 publications
3
29
1
Order By: Relevance
“…The most commonly studied of these fitness-related traits are locomotor performance, in terms of maximum burst speed or endurance/stamina (Walton, 1988;Kolok, 1992;Austin & Schaffer, 1992;Gibson & Johnston, 1995;Gregory & Wood, 1998;Kolok et al, 1998), and aerobic metabolism, in terms of maximum oxygen consumption rates (Hayes & Chappell, 1990;Friedman et al, 1992;Chappell et al, 1995), field metabolic rate (Berteaux et al, 1996;Peterson et al, 1998), resting metabolic rate (DeVera & Hayes, 1995) and SMR (O'Connor et al, 2000). To my knowledge, this is the first study to examine the consistency of individual variation in aerobic metabolism (SMR) over time during a period of sustained growth (the salmon increasing 20-fold in mass between measurements) and the first during a period when a key life history decision (early/delayed migration in Atlantic salmon) is being made.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly studied of these fitness-related traits are locomotor performance, in terms of maximum burst speed or endurance/stamina (Walton, 1988;Kolok, 1992;Austin & Schaffer, 1992;Gibson & Johnston, 1995;Gregory & Wood, 1998;Kolok et al, 1998), and aerobic metabolism, in terms of maximum oxygen consumption rates (Hayes & Chappell, 1990;Friedman et al, 1992;Chappell et al, 1995), field metabolic rate (Berteaux et al, 1996;Peterson et al, 1998), resting metabolic rate (DeVera & Hayes, 1995) and SMR (O'Connor et al, 2000). To my knowledge, this is the first study to examine the consistency of individual variation in aerobic metabolism (SMR) over time during a period of sustained growth (the salmon increasing 20-fold in mass between measurements) and the first during a period when a key life history decision (early/delayed migration in Atlantic salmon) is being made.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional procedures for the assessment of behavioral endpoints, such as the measurement of swimming performance, were often found to be relatively insensitive [11,[17][18][19][20]. Differences in the exploratory power of the two ap-proaches (a means comparison and an individual approach) have been analyzed very recently with respect to individual variation in the swimming performance [21]. Behavioral approaches employing indication criteria other than swimming performance proved to be toxicologically more sensitive but did not provide for continuous monitoring or longer-term observations (e.g., ventilation frequency [22] and preferenceavoidance response [23]).…”
Section: Discussionmentioning
confidence: 99%
“…The fish were then weighed and a fin clipped for identification of individuals. Previous studies have found that the paired pelvic fins and the single anal fin could be clipped from the fish without influencing U crit [10].…”
Section: Methodsmentioning
confidence: 99%